Portuguese expatriates and their international work experiences. - Coelho, J. V. (XI Congresso Português de Sociologia, 2021)
Prevailing organizational and management discourses tend to present global employment practices and international mobility as stimulating and distinguishing experiences. In this regard, it is said to be important to gain international work experience, to go abroad, and leave one’s comfort zone. Leaving and living abroad is portrayed in a favorable light, as both an opportunity and a desirable choice that allows workers to grow professionally. However, in contrast, from an individual, lived perspective, stories of failure, contradiction and paradox are observed, as well as concrete difficulties in fully integrating an expatriate experience.This presentation reports the results of a Phd study, where expatriation was taken as empirical reference to enquiry contemporary international work and employment practices. In particular, the subjective sense of ambivalence that tends to be associated with the representation of an expatriation as a work arrangement used to anchor business internationalization processes constitutes the problematizing axis of the research reported by the presentation.24 individual expatriation experiences, observed in five different multinational firms founded or located in Portugal, were studied. Analytical results suggest that living and performing work in an expatriate context can foster individual and social differentiation, as reported lived experiences don`t necessarily imply homogeneity, conformity, personal growth or an enriched lifestyle. Differentiation, in specific contexts and cases, arises unexpectedly, for both companies and individuals. Three types of expatriate experience are proposed and described in detail, involving divergent modes to relate with an expatriation setting: normative integration for conformist expatriates; self-serving strategy for protean expatriates; and defensive distancing for stationary expatriates.